What it takes to do the double jaeger on the high bar? - Heinen, T.; Jeraj, D.; Vinken, P. M.; Knieps, K.; Velentzas, K.; Richter, H. (Science of Gymnastics Journal, 2011)
Nowadays, the Jaeger (forward salto behind the bar to regrasp) is seen as a basic flight element, already taught early in a gymnast`s career. Acknowledging, that gymnasts have made advances in the development of new techniques on the high bar, the aim of the present study was to show that the double Jaeger is actually possible to be performed, and to specify the mechanical conditions one athlete must provide to have the competence to perform. A computer simulation model was used to investigate the mechanical conditions of different variants of the double Jaeger (tucked and piked). Input to the model comprised a national level gymnast`s segmental inertial parameters, and the gymnast`s performance in terms of the calculated and smoothed angle-time histories of Jaeger and Gaylord performances. Initial conditions consisted of the gymnast`s vertical and horizontal release velocities of the center of mass, the angular velocity about the transverse axis, and the joint angles at release. Model output comprised the resulting motion of the gymnast. A systematical variation of the skill`s parameter space led to a total of n = 940896 simulations. From these, 3.26% were successful for the double tucked Jaeger, and 2.50% were successful for the piked variant. Due to the simulation it can be concluded, that the double Jaeger is a hypothetically feasible skill for gymnasts who can produce a defined angular momentum together with a defined time of flight.